A Hepatoprotective Effect of Extract Ethanol Gynura procumbens on Liver Injury Induced by Toxic Dose of Paracetamol - Sri Almarahma; Peter Kabo; Yulia Yusrini Djabir (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2022)
Gynura procumbens is a plant that contains flavonoid compounds as antioxidants and has a hepatoprotective effect. A hepatoprotector is a compound that can protect the liver from liver damage. One way to determine liver function is to measure the enzyme activity of Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT). This study aimed to determine the hepatoprotective effect of the extract ethanol of Gynura procumbens on the liver induced by paracetamol toxic dose. This study used 20 white male rats divided into five groups: positive control group, negative control (NaCMC 1%), and paracetamol dose of 2.400mg/kg bw). EDSNY 100 mg/kg bw, 200 mg/kg bw, 300 mg/kg bw + 2.400 mg/kg paracetamolThe rat blood samples were taken through the lateral vein, and then the SGOT and SGPT were measured before, after 4 days, and on the 6th day after paracetamol induction. The results showed that the ethanol extract of Gynura procumbens significantly reduced the levels of SGPT in mice at a dose of 300 mg/kg bw. However, the ethanol extract of Gynura procumbens leaves could not reduce SGOT levels in rats. From the histopathological results, it was evident that both low, medium, and high doses had not been able to significantly improve liver damage induced by toxic doses of paracetamol. However, the ethanol extract of Gynura procumbens leaves appeared to reduce the number of areas of necrosis and degeneration of hepatocytes compared to the negative control group. Based on the study's results, the ethanol extract of Gynura procumbens leaves at a dose of 300 mg/kg bw was able to protect against an increase in SGPT. Still, it hadn't shown that it was the best way to protect the liver from damage caused by too much paracetamol.